Спектри дифузного відбивання нанопорошків TiO₂ та V₂O₅ - Шевчук, В.; Попович, Д.; Белюх, В.; Усатенко, Ю. (Праці наукового товариства ім. Шевченка, 2011)
Diffuse reflectance spectra of nanopowders TiO₂ (dominant phase is rutile) V₂O₅, and nanocomposites TiO₂/ Cr₂O₃, TіO₂/MnO₂, TіO₂/V₂O₅ in spectral region 400-750 nm at room temperature were investigated. The d ions were controlled by electron paramagnetic resonance method. The experimental data were analyzed within the framework of Kubelka-Munk theory In doped TiO₂, the shift of intensive optical absorption edge the appearance of addition absorption bands in extrinsic region and fading in spectral area 400-460 nm for nanocomposite TiO₂/ MnO₂ were registered. The band gap of TiO₂, V₂O₅, and nanocomposites based on these powders were evaluated by difference methods .